Active listening techniques in the language skills of the upper basic of the San Cayetano Chone educational unit - Moreira, Diana Magaly Moreira; Montes, Lubis Carmita Zambrano (Linguistics and Culture Review, 2021)
Active listening is a necessary aspect to develop in students with this, positive relationships are created within the classroom, achieving conflict resolution. The objective of this research was to identify the creative active listening techniques used by teachers to improve the language skills of students at the San Cayetano de Chone Educational Unit, Ecuador. The study was carried out under a quantitative - qualitative descriptive and exploratory approach. To collect the information, the bibliographic study and the survey technique were used. The results show inadequacies in the management of language skills for active listening in students. It is concluded that students present some degree of difficulty to communicate effectively with other people. Most of the teachers apply methodological strategies for the linguistic development of the students; However, it is necessary to apply innovative techniques to improve active listening in students, since the students admitted to a certain degree having flaws in the management of language skills, on the other hand they consider that the authorities of the educational institution are working to improve methodological strategies for the development of active listening in students.